Inhibition of pulmonary artery smooth muscle cells via the delivery of curcuminoid WZ35 by Cu‐based metal organic frameworks - Zhidan Hua; Mingming Han; Lanlan Song; Yongle Yan; Honglang Chen; Jilong Wang; Chao Li; Yanfan Chen; Hanhan Yan; Mayun Chen (IET Nanobiotechnology)
Abstract Hypoxic pulmonary hypertension (HPH) is a life‐threatening disease that occurs due to a lack of oxygen in the lungs, leading to an increase in pulmonary vascular resistance, right ventricular failure, and ultimately death. HPH is a multifactorial disorder that involves multiple molecular pathways, making it a challenge for clinicians to identify effective therapies. Pulmonary artery smooth muscle cells (PASMCs) play a crucial role in HPH pathogenesis by proliferating, resisting apoptosis, and promoting vascular remodelling. Curcumin, a natural polyphenolic compound, has shown potential as a therapeutic agent for HPH by reducing pulmonary vascular resistance, inhibiting vascular remodelling, and promoting apoptosis of PASMCs. Regulation of PASMCs could significantly inhibits HPH. However, curcumin has the disadvantages of poor solubility and low bioavailability, and its derivative WZ35 has better biosafety. Here, Cu‐based metal organic frameworks (MOFCu) was fabricated to encapsulate the curcumin analogue WZ35 (MOFCu@WZ35) for the inhibition of PASMCs proliferation. The authors found that the MOFCu@WZ35 could promote the death of PASMCs. Furthermore, the authors believed that this drug delivery system will effectively alleviate the HPH.